(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
The article analyzes the interaction of various temporal and spatial layers inM. A. Bulgakov’s novel "The Master and Margarita" as one of the key principles of artistic organization of the work. The relevance of the research is due to the steady interest of modern literary studies in the problem of chronotope and intertextuality, as well as the need to rethink the novel in the context of philosophical and aesthetic searches of the twentieth century.The aim of the study is to identify the specifics of the correlation of the Moscow, biblical and mystical chronotopes and determine their role in revealing the ideological and philosophical content of the novel.